2021
DOI: 10.1186/s40663-021-00290-3
|View full text |Cite
|
Sign up to set email alerts
|

Seamless integration of above- and under-canopy unmanned aerial vehicle laser scanning for forest investigation

Abstract: Background Current automated forest investigation is facing a dilemma over how to achieve high tree- and plot-level completeness while maintaining a high cost and labor efficiency. This study tackles the challenge by exploring a new concept that enables an efficient fusion of aerial and terrestrial perspectives for digitizing and characterizing individual trees in forests through an Unmanned Aerial Vehicle (UAV) that flies above and under canopies in a single operation. The advantage of such co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Previous standard errors obtained in the same site [35] have ranged from 5-6% (for backpack and hand-held laser scanning) up to 6-8% (for high-density abovecanopy UAV laser scanning data). In Wang et al [25], the standard error of tree heights estimated from UAV data was 6.1% for trees with a DBH exceeding 15 cm, which is similar to the results reported in [35]. Our results imply that under-canopy UAV laser scanning may provide tree height estimates with a slightly better accuracy than conventional highdensity above-canopy UAV laser scanning measurements.…”
Section: Tree Height Estimationsupporting
confidence: 86%
See 2 more Smart Citations
“…Previous standard errors obtained in the same site [35] have ranged from 5-6% (for backpack and hand-held laser scanning) up to 6-8% (for high-density abovecanopy UAV laser scanning data). In Wang et al [25], the standard error of tree heights estimated from UAV data was 6.1% for trees with a DBH exceeding 15 cm, which is similar to the results reported in [35]. Our results imply that under-canopy UAV laser scanning may provide tree height estimates with a slightly better accuracy than conventional highdensity above-canopy UAV laser scanning measurements.…”
Section: Tree Height Estimationsupporting
confidence: 86%
“…Let us then compare our stem detection results against those reported in previous studies using under-canopy UAVs for forest field reference measurements [16,25]. The studies in [16] were conducted on the same test sites as the current study.…”
Section: Completeness and Correctness Of Stem Detectionmentioning
confidence: 85%
See 1 more Smart Citation
“…Above-canopy data could be used to complement the terrestrial viewpoints as shown in Bienert et al (2010) , with above-canopy scans from towers or with intracanopy scans acquired using a drone. Wang et al (2021) present intra- and above-canopy drone flights and compare them with ground-based TLS scans. The dense point clouds in the upper crown area have a geometric accuracy comparable with those from MLS data and have an RMSE of the DBH of 2–4 cm and of the stem curve of 4–7 cm.…”
Section: Introductionmentioning
confidence: 99%
“…While TIR has been demonstrated readily capable of identifying stream network extension in bare/unforested regions (such as those common in parts of Europe or high arctic locations), forested regions present a problem whereby dense tree canopies limit the ability of TIR sensors to resolve ground‐level hydrological properties, particularly in coniferous woodland where winter leaf loss does not occur. While understory drone acquisition flights are technically possible (e.g., Hyyppä et al., 2020; Wang et al., 2021), this introduces a substantial risk to both equipment and researchers and is unlikely to provide a universal solution. Research is therefore needed to understand the accuracy with which headwater network extension/surface saturation dynamics can be quantified as a function of varying forest density, as well as the potential for fusion of ground‐ and drone‐based data to provide seamless coverage in areas of patchy forest.…”
Section: Leveraging Drone‐based Technologiesmentioning
confidence: 99%